Isolation and Identification of Cellulolytic and Lignolytic Bacteria from the Gut Oryctes rhinoceros L. Larvae Decomposition of Oil Palm Empty Fruit Bunches - Dini, Isna Rahma; Wawan, Wawan; Hapsoh, Hapsoh; Sriwahyuni, Sriwahyuni (Indonesian Journal of Agricultural Research, 2018)
One of the organisms that helps in decomposition of oil palm empty fruit bunches is Oryctes rhinoceros L. larvae. This is because of in the gut of the larvae there are many cellulolytic bacteria and lignoliytic. The process of accelerating the decomposition of oil palm empty fruit bunches into compost can be done by optimizing the work of the bacteria. The aim of this research is to obtain cellulolytic and lignolytic bacteria from larvae O. rhinoceros L.. The research succeeded to isolate 24 isolates of cellulolytic bacteria and lignolytic bacterial isolates from the gut of O. rhinoceros larvae. Based on qualitative test, 9 isolate bacteria produced cellulolytic index above 2. The highest cellulolytic index was generated by ORL19 isolate, while the lignolytic index obtained ORL6 isolate. Based on macroscopic and microscopic identification of bacteria, biochemical and physiological tests, it was found ORL 6 belongs to the genus Bacillus sp. while the ORL 19 belongs to the genus Citrobacter sp..